DUSP15 expression is reduced in the hippocampus of Myrf knock-out mice but attention and object recognition memory remain intact - Rawlings-Mortimer, F; Gullino, LS; Rühling, S; Ashton, A; Barkus, C; Johansen-Berg, H (Public Library of Science, 2023)
The atypical protein tyrosine phosphatase enzyme, dual-specificity phosphate 15 (DUSP15) is thought to be activated by myelin regulatory factor (MyRF) and to have a role in oligodendrocyte differentiation. Here, we assess whether Dusp15 is reduced in the hippocampus of mice with conditional knock-out of Myrf in oligodendrocyte precursor cells. Using quantitative polymerase chain reaction (qPCR) we found that Dusp15 expression was indeed lower in these mice. Alterations in myelin have been associated with Alzheimer's disease (AD), autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD). Symptoms of these disorders can include impairments of object recognition and attention. We, therefore tested the mice in the object recognition task (ORT) and 5-choice serial reaction time task (5CSRTT). However, we did not find behavioural impairments indicating that attentional abilities and object recognition are not impacted by reduced oligodendrogenesis and hippocampal Dusp15 expression. Gaining insight into the role of newly formed oligodendrocytes and Dusp15 expression is helpful for the development of well targeted treatments for myelin dysregulation.